2021
DOI: 10.3390/jof7030173
|View full text |Cite
|
Sign up to set email alerts
|

Local Tree Diversity Suppresses Foliar Fungal Infestation and Decreases Morphological but Not Molecular Richness in a Young Subtropical Forest

Abstract: Leaf fungal pathogens alter their host species’ performance and, thus, changes in fungal species composition can translate into effects at the tree community scale. Conversely, the functional diversity of tree species in a host tree’s local neighbourhood can affect the host’s foliar fungal infestation. Therefore, understanding the factors that affect fungal infestations is important to advance our understanding of biodiversity-ecosystem functioning (BEF) relationships. Here we make use of the largest BEF tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 93 publications
1
3
0
Order By: Relevance
“…Our main findings, however, confirmed neither the published positive [15] or negative effects of tree diversity on FEF diversity [17]. Such an inconsistency in host-endophyte diversity relationships has also been reported from samples of Norway spruce in mature forests [38] and from the largest subtropical tree diversity experiment in China [18].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our main findings, however, confirmed neither the published positive [15] or negative effects of tree diversity on FEF diversity [17]. Such an inconsistency in host-endophyte diversity relationships has also been reported from samples of Norway spruce in mature forests [38] and from the largest subtropical tree diversity experiment in China [18].…”
Section: Discussionsupporting
confidence: 57%
“…In a three-year-old and more sparsely planted experiment in the US, Griffin et al [17] found the opposite relationship. In the largest tree diversity experiment in China, Saadani et al [18] found that foliar fungi in general (including endophytic and pathogenic species) were not affected by the diversity of the tree neighborhood. Tentatively, one might speculate that the effects of tree diversity on FEF might increase with the age and the density of the planted trees.…”
Section: Introductionmentioning
confidence: 99%
“…and in nearby natural forest stands (Brezzi et al, 2017). In contrast, foliar fungal infestation in the experiment was suppressed by tree diversity (Saadani et al, 2021). Taken together, these observations suggest that leaf fungi benefited from higher host densities in monoculture, and their suppression therefore led to increased productivity at low diversity and a weakened species-richness effect at the community-level.…”
Section: Discussionmentioning
confidence: 73%
“…Similar positive effects of tree species richness on herbivores and herbivory were observed in the additional plots of the BEF‐China experiment referred to above (Schuldt et al, 2017), in plots with a higher genetic diversity within species (Hahn et al, 2017), and in nearby natural forest stands (Brezzi et al, 2017). In contrast, foliar fungal infestation in the experiment was suppressed by tree diversity (Saadani et al, 2021). Taken together, these observations suggest that leaf fungi benefited from higher host densities in monoculture, and their suppression therefore led to increased productivity at low diversity and a weakened species‐richness effect at the community‐level.…”
Section: Discussionmentioning
confidence: 99%